Relationship between Dental Caries Experience and the Levels of Streptococcus mutans and Lactobacillus in Saliva of Pregnant Women : Caries and cariogenic microorganisms in pregnant women - Jalal Hussein, Fighan; Sherdl Saleem , Sazan; Abdulaziz Merdad, Khalid (Cellular and Molecular Biology, 2023)
Pregnancy-related changes may increase the risk of dental caries. The Cariogram software program was created to understand this risk better. This study aims to correlate dental caries experience with Streptococcus mutans and lactobacillus levels in saliva using real-time PCR. This case-control analytical study conducted in Erbil City, Iraq, between 2021 and 2023 used a Cariogram to assess tooth decay risk and a real-time PCR assay to detect oral bacteria. Kurdish chewing gum with oil extract was used to stimulate saliva production. The chance of preventing tooth decay was 50.57% in pregnant women and 60.26% in non-pregnant women, with a statistically significant difference. The correlation between caries risk categories and Streptococcus mutans and Lactobacillus levels in saliva was significant but weakly positive, with strengths of 0.295 and 0.213, respectively. Furthermore, the proportion of pregnant women with Lactobacillus class 2 or Lactobacillus class 3 was significantly higher than that of non-pregnant women (7% and 10% versus 2% and 1%, respectively) with a p of 0.001. The study also found that 82% of pregnant women had a very low or zero amount of Streptococcus mutans compared to 96% of non-pregnant women (p = 0.011). The study concluded that Streptococcus mutans and Lactobacillus (SM and LBs) could be accurately detected through qPCR, and their counts have a significant positive correlation with caries risk categories. These bacteria are considered important causal agents of dental caries, especially in pregnant women.